The evidence for conjugated mandelic and phenylglyoxylic acids in the urine of rats dosed with styrene - Linhart, I; Weidenhoffer, Z; Mráz, J; Smejkal, J; Mládková, I (Toxicology letters, 1997)
Male Wistar rats were dosed intraperitoneally with styrene (400 mg/kg). Urine samples were collected over phosphate buffer, pH 6.5 for 24 h. Excretion of mandelic (MA) and phenylglyoxylic acid (PGA) amounted to 1.66 +/- 0.62 and 5.21 +/- 2.44% of dose, respectively, as determined by ion-pair HPLC. After acidic hydrolysis, the amount of MA and PGA found in urine increased to 2.10 +/- 0.84 and 6.81 +/- 3.20% (mean +/- S.D.; n = 7), respectively. A similar increase was observed after alkaline hydrolysis of urine samples. Differences between hydrolysed and non-hydrolysed samples were significant in the paired t-test (P < 0.05). Further, urine samples were fractionated by HPLC. Fractions were subjected to acidic hydrolysis and analysed by HPLC and GC/MS. Both MA and PGA were detected in the fraction which did not contain any of these metabolites before hydrolytic treatment. Thus, MA and PGA, which are used as biomarkers of exposure to styrene, form hydrolysable conjugates in the rat. At least a minor part of the total urinary MA and PGA is bound in these conjugates.
Keywords: styren; styreny; Male; Rats, Wistar; plynová chromatografie s hmotnostně spektrometrickou detekcí; Styrene; mužské pohlaví; potkani Wistar; Mandelic Acids; glyoxyláty; Gas Chromatography-Mass Spectrometry; krysa rodu Rattus; Animals; proteinurie; injekce intraperitoneální; biopolymery; Injections, Intraperitoneal; zvířata; Biopolymers; Rats; Glyoxylates; Styrenes; Proteinuria; kyseliny mandlové